Literature and consciousness. An exploration from the cognitive sciences. Introduction - Gamoneda Lanza, Amelia; Cheguhem, Mauricio (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
Introduction of the dossier on the study of the implications in Literature of notions and aspects of consciousness contributed from Cognitive Sciences